2005
DOI: 10.1128/aem.71.7.4153-4155.2005
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Microbiota Signatures across Five Northern European Countries

Abstract: The composition of the colonic microbiota of 91 northern Europeans was characterized by fluorescent in situ hybridization using 18 phylogenetic probes. On average 75% of the bacteria were identified, and large interindividual variations were observed. Clostridium coccoides and Clostridium leptum were the dominant groups (28.0% and 25.2%), followed by the Bacteroides (8.5%). According to principal component analysis, no significant grouping with respect to geographic origin, age, or gender was observed.For the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
194
1
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(212 citation statements)
references
References 15 publications
(12 reference statements)
12
194
1
5
Order By: Relevance
“…These data were significant for the virome contents in both males (P ¼ 0.0121) and females (P ¼ 0.0034) ( Table 2 and Supplementary Table 2). Differences between the sexes in bacterial communities previously have been demonstrated for the human gut microbiome (Mueller et al, 2006;Li et al, 2008) and the subgingival crevice (Schenkein et al, 1993;Lay et al, 2005). The data presented here (Table 2) suggest that sex-based differences observed in bacteria also apply to communities of human viruses.…”
Section: Inter-and Intrasubject Comparisons Of Viral Genotypessupporting
confidence: 55%
“…These data were significant for the virome contents in both males (P ¼ 0.0121) and females (P ¼ 0.0034) ( Table 2 and Supplementary Table 2). Differences between the sexes in bacterial communities previously have been demonstrated for the human gut microbiome (Mueller et al, 2006;Li et al, 2008) and the subgingival crevice (Schenkein et al, 1993;Lay et al, 2005). The data presented here (Table 2) suggest that sex-based differences observed in bacteria also apply to communities of human viruses.…”
Section: Inter-and Intrasubject Comparisons Of Viral Genotypessupporting
confidence: 55%
“…Prevotella has been found to be a minor component of Japanese gut microbiota (42), and is considered to be difficult to detect by the T-RFLP method. While some studies suggest that the gender of the host has an effect on the gut microbiota (43), other studies suggest that gender has no effect (44). For example, previous studies have reported that the BacteroidesPrevotella groups are more abundant in the gut microbiota of males than females from European locations (45).…”
Section: Discussionmentioning
confidence: 92%
“…For example, microbial communities of monozygotic twins have a higher similarity to each other than their marital partners, indicating a strong influence of the host genotype (Zoetendal et al, 2001). Similarly, a large individual variability, which could not be explained by geographic origin, age or gender, has been reported (Lay et al, 2005). In addition, microbial community composition in the intestine depends to a large extent on the supply of dietary carbohydrates that resist digestion in the upper tract, and it is conceivable that diets have an impact on bacterial community composition (Gibson et al, 1995;Kleessen et al, 2001;Duncan et al, 2003).…”
Section: Discussionmentioning
confidence: 95%